PENGARUH SUKU BUNGA, INDEKS HARGA KONSUMEN DAN KURS TERHADAP JUMLAH KREDIT TOTAL DAN PERTUMBUHAN EKONOMI BALI - Maharani, Desak Putu Putri; Setiawina, Nyoman Djinar; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.03.TAHUN 2017, 2017)
Economic growth is a change in the level of economic activity that lasts from year to year. An economy is said to be experiencing a change in its development if the level of economic activity is higher than that achieved in the previous period. For that research conducted in the province of Bali from 2004 to 2015. As stipulated in Law No. 10 of 1998, which meant the bank is an entity that collects funds from the public in the form of savings and channel them to the public in the form of loans and or shape other-shape in order to improve the standard of living of the people (Kashmir, 2008). Thus, the bank is part of a financial institution intermediary function that bridges the benefit of the excess funds (depositors or creditors) and those who need the funds (the borrower or debtor). To improve and Economic Growth and Total Total Credits can be pursued through the interest rate, Consumer Price Index and the exchange rate.
Keywords: Economic Growth, Total Credit Amount, Interest Rate, the Consumer Price Index, Exchange